2018
DOI: 10.4314/mmj.v30i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Clients with stroke and non-stroke and their guardians’ views on community reintegration status after in-patient rehabilitation

Abstract: AimThe aim of this study was to compare client community reintegration status following discharge from the Kachere Rehabilitation Centre (KRC), Blantyre, Malawi, in 2 consecutive years with client versus guardian perspectives on reintegration status.MethodsUsing quantitative methods, 35 clients with stroke and non-stroke diagnoses (spinal cord dysfunction and neuropathic conditions) and 32 client guardians (the family caregivers in Malawi) were separately interviewed using the WHO Disability Assessment Schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…In urban South Africa, after at least 6 months following a stroke, 43% of people felt that they had achieved no or minimal re-integration with their families, with particular difficulties reported around being unable to take on family responsibilities or return to work [24]. Similar patterns of participation restriction were reported post-stroke in Malawi in 2018 [25]. In Nigeria, a qualitative study examining the experience of life after stroke found that participants reported “I cannot visit the market as usual; now my outing has been restricted to only once a week” , “I am cut-off from social visits” , and “the only thing I can do now is to sit and look” [26].…”
Section: What Is the Association Between Ncds And Disability?mentioning
confidence: 97%
“…In urban South Africa, after at least 6 months following a stroke, 43% of people felt that they had achieved no or minimal re-integration with their families, with particular difficulties reported around being unable to take on family responsibilities or return to work [24]. Similar patterns of participation restriction were reported post-stroke in Malawi in 2018 [25]. In Nigeria, a qualitative study examining the experience of life after stroke found that participants reported “I cannot visit the market as usual; now my outing has been restricted to only once a week” , “I am cut-off from social visits” , and “the only thing I can do now is to sit and look” [26].…”
Section: What Is the Association Between Ncds And Disability?mentioning
confidence: 97%
“…One crucial point for conducting readiness assessment is before discharge to home from inpatient rehabilitation setting. 6 Building on work done by researchers describing stroke survivors' needs related to re-integration into community post-discharge, 45 and caregivers' needs related to caregiving and facilitating community transition, 46 readiness assessment at discharge should focus on stroke survivors' functional needs, community re-integration challenges, caregivers' commitment and capacity to care (ie, assessing for pre-existing health issues and self-care strategies), prior caregiving experience, available resources and overall impact of stroke. 46 study limitations Following are the limitations.…”
Section: Discussionmentioning
confidence: 99%
“…41 Increasing community engagement after stroke presents a myriad of challenges, 42 including barriers to engagement because of changes in mobility and self-efficacy with balance, 43 cognitive 44 , language and visual impairment; reduced access to transportation; and psychosocial factors, such as reduced confidence with selfimage. 45 However, community reentry is often a goal for people with stroke and is valued as a mark of independence as well as a modality for continuity of holistic maintenance and remediation of various personal functions.…”
Section: Potential Problems Related To Public Health Effortsmentioning
confidence: 99%